Development of electrocoagulation cell by using different types of electrode materials to treat restaurant wastewater - Chong, Li Ping (2019)
Electrocoagulation cell (EC) is a technology to remove pollutants from wastewater which involve electric current into an aqueous medium using electrode. Development of EC by using different types of electrode materials to treat restaurant wastewater was investigated in this study. Two types of electrodes materials were used such as Aluminums (Al) and Iron (Fe) to determine the removal efficiency of biological oxygen demand (BOD), chemical oxygen demand (COD) and total suspended solids (TSS). Four experiments were run out by using different combination of electrode materials at anode and cathode which were Al-Al, Fe-Fe, Al-Fe and Fe-Al. The operating parameters such as inter-electrode distance, treatment duration, current intensity were fixed at 10mm, 120 minutes and 3A respectively. The highest removal for BOD (98%), COD (91.4%) and TSS (86.9%) was obtained by Al-Fe among four electrode types. Meanwhile, the lowest electrode pairs were recorded by Al-Al with a value of 70.9%, 85.7% and 64.4% for BOD, COD and TSS respectively. Besides, Fe-Al electrodes showed a result of 80.7%, 96.7% and 63.0% of BOD, COD and TSS removal efficiency respectively. Last but not least, Fe-Fe electrodes achieved 80.6%, 95.7% and 61.5% efficiency removal of BOD, COD and TSS. This result can be explained by process occurred at anode and cathode. Al performed good at anode as it released trivalent ion (Al3+) instead of divalent ion (Fe2+) by iron electrode. Higher positive charge had higher ability to destabilise the colloids. While, Fe was better at cathode because it released small size but large amount of bubbles which helped in removing suspended solids and formed flocculation. The amount of Al dissolution was 0.102 g while Fe recorded 0.801 g which meant Al released more trivalent ion to coagulate the pollutant in restaurant wastewater. The experiments result showed efficient removal of BOD, COD and TSS by EC with Al and Fe electrodes.